The Influence of Policy on the Development of Student Competence at Al Idris Islamic Boarding School: Integration of TPB Through the PLS-SEM Approach - Rasid, Sulaiman Abdul; Ardiansyah, Dedi; Harwi, Andreas Fredyansa; Al Azhari, M. Fadli (Journal of Educational Sciences, 2025)
This research examines the influence of Islamic boarding school policies on student competency development at Al Idris Islamic Boarding School. Using the Theory of Planned Behavior (TPB) and PLS-SEM methodology, the study involved 54 students selected through purposive sampling. Analysis results reveal that self-awareness plays a crucial role as a mediator between boarding school policies and TPB in enhancing student competencies. The indirect effect of boarding school policies on competency development through self-awareness showed values of β = 0.134 (T-Statistics = 2.085; P-Value = 0.038), while the indirect effect of TPB on competency development through self-awareness yielded β = 0.337 (T-Statistics = 2.248; P-Value = 0.025). These findings highlight the importance of strengthening policies in Islamic boarding schools that foster student self-awareness. Recommendations include improving self-reflection-based learning systems, providing motivational support from religious teachers (kiai and ustaz), and integrating life skills into the curriculum. With appropriate policies, Islamic boarding schools can prepare students to excel not only in Islamic knowledge but also in competencies relevant to contemporary challenges.